The Role of Women Entrepreneurs in Establishing a Sustainable Development in Sri Lanka - Ambepitiya, K.R. (Faculty of Commerce and Management Studies, University of Kelaniya, 2015)
Woman has become a significant role in the economic development of any country. They contribute and support the economy extensively is different ways of being employed in different sectors. There are many women running successful businesses and some of them are very successful with entrepreneurial skills. It is a known fact that now many successful and world’s enormous enterprises are owned and run by women. Many of them are actual or potential owners of trademarks, service marks, trade name as well as of industrial designs, patents and copyright. In developing countries some women are running small enterprises and many cooperatives that are proving so successful. Women entrepreneurs in both developed and developing countries are, socially powerful in education and making a positive impact to the society. It is important to study how women in business and their skills can be utilized in order to achieve a sustainable economy for Sri Lanka. The objectives of this study have scattered in the study of women entrepreneurs to a sustainable economy, social system, and ecology. A descriptive research methodology is used for this study and administered to a selected sample from a specific population included with women in businesses and executives who are from private and public sector offices. The study consists of six month duration which uses a questionnaire as the survey instrument. Using the survey, it has resulted significantly the women entrepreneurs can be positioned to play an important role in promoting sustainable practices in economics, social system and ecology, to result a sustainable development. The researcher concludes the study by observing the positive effect on the economy and the development, the Women entrepreneurship is a key to the developing world to promote sustainable practices in business.
Keywords: Entrepreneurship; Sustainable Development; Women in Business; Economy; Development